Fluid management of shock in severe malnutrition: what is the evidence for current guidelines and what lessons have been learned from clinical studies and trials in other pediatric populations? - Obonyo,N; Maitland,K (Food and Nutrition Bulletin, 2014)
Management of shock in children with severe malnutrition remains controversial. To date, the evidence supporting either benefit or harm of fluid resuscitation or rehydration is weak. This issue, however, is not unique to children with severe malnutrition; pediatric guidelines worldwide have a weak level of evidence and remain unsupported by appropriate clinical studies. In this review we give an overview of the current recommendations in other pediatric populations and appraise the strength of evidence supporting these. We summarize results from the only controlled trial ever undertaken, FEAST (Fluid Expansion As Supportive Therapy), which was conducted in resource-poor hospitals involving 3,141 African children with severe febrile illnesses and shock, including large subgroups with sepsis and malaria but excluding children with severe malnutrition. This high-quality trial provided robust evidence that fluid resuscitation increased the risk of death, leading to an excess mortality of 3 in every 100 children receiving fluid boluses, compared with controls receiving no boluses. These findings may have particular relevance to management of septic shock in children with severe malnutrition. However, they cannot be extrapolated to children with gastroenteritis, since this condition was not included in the trial. Current observational studies under way in East Africa may provide insights into myocardial and hemodynamic function in severe malnutrition, including responses to fluid challenge in those complicated by gastroenteritis. Such studies are an essential step for setting the research agenda regarding fluid management of shock in severe malnutrition.